2004
DOI: 10.1021/ef049946a
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbon-Catalyzed Hydrogenation of Polycyclic Arenes

Abstract: Benzene and four polycyclic arenes (PAs) were used as substrates and their hydrogenation reactions were conducted over activated carbon (AC) at 300 °C to examine the relationship between their molecular structures and reactivities. The results show that the AC catalyzed the hydrogenation of the PAs selectively and that the reactivities of the arenes toward hydrogenation were dependent on the hydrogen-accepting abilities of the arenes and on the adsorption strengths of the arenes on the catalyst surface. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Unfortunately, when using alumina-supported catalysts, the presence of weak Lewis-type acidic sites on the support surface leads to accumulation of unwanted coke deposits. 7 In order to substitute the standard Al 2 O 3 support, the use of less acidic or neutral supports such as silica, K-modified alumina, mesoporous silicas (MS) or activated carbon for the HDO [8][9][10][11][12] and HDA [13][14][15] reactions has been studied. In particular, the SBA-15 substrate having hexagonal pores in a 2D array with long 1D channels (P6mm plane group) proved to be effective for supporting CoMo sulphide phases tested in bio-oil upgrading.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, when using alumina-supported catalysts, the presence of weak Lewis-type acidic sites on the support surface leads to accumulation of unwanted coke deposits. 7 In order to substitute the standard Al 2 O 3 support, the use of less acidic or neutral supports such as silica, K-modified alumina, mesoporous silicas (MS) or activated carbon for the HDO [8][9][10][11][12] and HDA [13][14][15] reactions has been studied. In particular, the SBA-15 substrate having hexagonal pores in a 2D array with long 1D channels (P6mm plane group) proved to be effective for supporting CoMo sulphide phases tested in bio-oil upgrading.…”
Section: Introductionmentioning
confidence: 99%
“…52,53 Activated carbon (AC) catalyzes monatomic hydrogen transfer, but such a hydrogen transfer did not lead to deep hydrogenation of polycyclic arenes. 98 Acidic supports improved the sulfur-resistance of metallic species and the catalytic activity for arene hydrogenation was modified as well, which was interpreted by the model of electron deficient 'metal-proton' adduct. 52,53,99 The mechanism for the interaction between Pt species and the zeolite was proposed.…”
Section: Supportsmentioning
confidence: 98%
“…Hydrogenation of aromatic compounds is an increasingly prominent class of hydrotreating reaction in coal, petroleum industries and organic transformations in organic chemistry [171]. For instance, Sun et al [172,173] reported an efficient method for arenes and polycyclic arenes hydrogenation at 300 • C using ACs. Interestingly, based on the catalytic hydrogenation and the molecular structures, the relationship between the reactivities of aromatic rings and the mechanism for hydrogen transfer was discussed.…”
Section: Porous Carbon Nanocomposites For Catalysismentioning
confidence: 99%